1988
DOI: 10.1590/s0074-02761988000400018
|View full text |Cite
|
Sign up to set email alerts
|

Natural lectin activity in the haemolymph of Panstrogylus megistus (Heteroptera: Reduvidae)

Abstract: The haemolymph of Panstrongylus megistus showed a natural lectin activity for a wide range of vertebrate erythrocytes. Agglutination was observed against all vertebrate erythrocytes tested (human ABO, duck, rabbit, mouse, sheep, chicken and cow). Cow erythrocytes showed the lowest titre. Concerning human erythrocytes, the lectin activity was similar in the types A+, B+ and AB+ while the highest activity was observed in the type O+. Determination of minimal inhibitory concentrations was carried out with human e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…This is in line with research Gomes (1988) that examined the natural activity of lectins on haemolymph Pangstrongylus megistus through hemagglutinasi test, it was found that in the supernatant and pellet P. megistus contained lectin activity in which the highest hemagglutination titer test was obtained from rabbit erythrocytes.…”
Section: Table 2 Agglutionation Titer Using Vertebrate Erythrocytessupporting
confidence: 87%
“…This is in line with research Gomes (1988) that examined the natural activity of lectins on haemolymph Pangstrongylus megistus through hemagglutinasi test, it was found that in the supernatant and pellet P. megistus contained lectin activity in which the highest hemagglutination titer test was obtained from rabbit erythrocytes.…”
Section: Table 2 Agglutionation Titer Using Vertebrate Erythrocytessupporting
confidence: 87%
“…Soluble lectins occur in a variety of species (Gold and Balding, 1975;Yeaton, 1982;Ey and Jenkin, 1982;Vasta and Marchalonis, 1983;Ratcliffe, 1986;Ratcliffe et aL, 1996;Richards and Ratcliffe, 1990;Osir, et al, 1995). Agglutination of parasites and erythrocytes by lectins has been reported in DipteraGlossinidae (Ingram and Molyneux, 1988;1993;Osir et al, 1995;Maudlin and Welburn, 1994); sandflies (Wallbanks et al, 1986); black flies (Ham and Smail, 1988); mosquitoes (Mohammed and Ingram, 1994;Mohamed et al, 1992); and Hemiptera -reduviid bugs (Pereira et al, 1981;Gomes et al, 1988;Barrocco and Loch, 1988;Mello et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan tabel diatas, hasil uji HA diperoleh titer agglutinasi tertinggi dari uji menggunakan eritrosit vertebrata, dikarenakan lektin invertebrata (serangga) teragglutinasi terhadap molekul asing secara in vitro dengan menggunakan eritrosit vertebrata (Gul dan Uji Hemaglutinasi Assay pada Hemolimf Spodoptera exigua yang diberi Perlakuan Botani e- ISSN 2654-5160 p-ISSN 1411 Avyali, 2001). Dalam penelitian ini digunakan eritrosit kelinci karena hal ini sejalan dengan penelitian Gomes et al, (1988) yang meneliti aktifitas natural lektin pada hemolimf Pangstrongylus megistus melalui uji hemagglutinasi, menemukan bahwa pada supernatan dan pelet P. megistus terdapat aktifitas lektin dimana, titer hemagglutinasi tertinggi diperoleh dari hasil uji eritrosit kelinci.…”
Section: Prosedur Penelitianunclassified